Considerations on Public Integrity Standards for Romanian MPs - Cynthia Carmen CURT (Transylvanian Review of Administrative Sciences, 2018)
The paper analyzes the implementation and effectiveness of public integrity standards within the Romanian Parliament, in the respect of the rule of law principle and in terms of the parliamentary mandate legitimacy. The subject is approached in the light of the recent European Commission Verifi cation and Cooperation Mechanism (CVM) Reports on Romania, focusing on the legal framework for public integrity and high level corruption limitation measures. The study uses different perspectives: (1) an analysis of the legislation suffi ciency regulating MPs incompatibilities and confl icts of interests, (2) the transparency level of parliamentary procedures concerning the termination of the parliamentary mandate, (3) and the legal framework’s most important evolutions, in terms of MPs integrity standards. The study presents a critical overview of the recent amendments issued by MPs, in order to limit the impact of public integrity framework and to restrain the legal competences of the National Integrity Agency (NIA). The constitutional jurisprudence analysis brings an additional insight related to legislation stability and law implementation, in terms of the fi nal court decisions enforcement. Recent CVM reports on Romania (European Commission, 2014, 2015, 2016, and 2017) emphasize that political will and political commitment are decisive for the success of implementation and irreversibility of curbing corruption public policies and strategies. The article also inquires the feasibility of the main priorities of National Anti-Corruption Strategy (NAS) (2016-2020), in terms of promoting legislation stability and adopting a codifi cation of public integrity standards. The paper tries to evaluate the level of political commitment of the Parliament towards the enforcement of integrity legislation and irrevocability of anticorruption strategies and public policies. The conclusions propose legislative solutions in terms of raising public integrity standards. Also, the study assesses the viability of CVM removal hypothesis and inquires the possible consequences on rule of law guarantees of such a scenario.